Improving students' creative thinking capacity to meet social requirements in the XXI century - Nguyễn Công Đức (Tạp chí Nghiên cứu Khoa học Công đoàn, 2022)
In the 21st century, with the development of the knowledge economy, higher education is having positive innovations, directed directly at learners, in order to educate people of the new era - global citizens. As the Resolution of the 13th National Party Congress clearly stated: “Training people in the direction of morality, discipline, discipline, sense of civic and social responsibility; have life skills, work skills, foreign languages, information technology, digital technology, creative thinking and international integration”. In order to improve the quality of training, the university teaching process not only stops at equipping knowledge, but also aims to develop students' thinking and practical ability. In particular, the ability to think critically plays a particularly important role, helping students improve their ability to apply learned knowledge to consider and evaluate learning problems fully, accurately and flexibly. and creativity.